Longevity of Shallow Subsurface Drip Irrigation Tubing under Three Tillage Practices. Issue 1 (12th June 2015) - Sorensen, Ronald B.; Lamb, Marshall C.
Abstract : Shallow Sub‐Surface drip irrigation (S 3 DI) has drip tubing buried about 2 inches below the soil surface. It is unknown how long drip tubing would be viable at this shallow soil depth using strip‐ or no‐tillage systems. The objectives were to determine drip tube longevity, resultant crop yield, and partial net revenue when using conventional, strip‐, and no‐tillage. Drip tubing (8, 10, and 15 mil) was buried 1.5 inches in 2006 and left in the field for five years under strip‐ and no‐till areas and removed and reinstalled in conventionally‐tilled areas. Crop rotation was cotton ( Gossypium hirsutum L.) the first year, corn ( Zea mays L.) the next three years, and peanut ( Arachis hypogaea L.) in the final year. There was no difference in cotton lint yield by tillage treatment and irrigated lint yield was 2.4 times greater than nonirrigated. There was no difference in irrigated corn yield across year or tillage practice. Irrigated corn yield was 5.8 times greater than nonirrigated yield. Irrigated peanut yield was the same across tillage treatments but was 2.6 times greater compared with nonirrigated yield. For tube longevity, conventionally tilled areas had less tube repairs compared with strip‐ or no‐tilled practices. Thinner wall tubing (8 mil) had 3.5 times more holes compared with thicker wall tubing (15 mil). The "cost‐to‐repair" versus "cost‐to‐replace" tubing indicates average replacement time at about 5.4 years. There were less production expenses for strip‐ and no‐ till compared with conventional tillage. Both strip‐ and no‐tillage systems are recommended when installing S 3 DI.